Investigations of factors affecting pendulum test value on asphaltic concrete surfaces - Baskara, Sudesh Nair (2009)
Skidding is one of the major contributions to road accidents during wet weather condition. Therefore, a study is conducted to investigate the factors affecting Pendulum Test Value on Asphaltic Concrete surfaces. The main objective of this study is to determine the mix type and the crossfall percentage that best resist skid during wet weather condition. Three different types of dense graded mixes were used in this study which are AC10, AC14 and AC20. Those three mixes are tested using Sand Patch Test (SPT) and are then subjected to various rainfall conditions and crossfall percentages using Rainfall Simulator. The rainfall conditions are categorized as low rainfall, medium rainfall and high rainfall while the crossfalls were increased 2% from 0% to 10% crossfalls. During the event of rainfall on each mix surfaces, a Portable Skid Resistance Tester is used on the mix to obtain the Pendulum Test Value (PTV) at different crossfalls. Results are analyzed using analysis of variance (ANOVA) to justify the objectives. Results from PTV shows that 4% to 10% crossfall and AC20 is the best crossfall and surface type in resisting skid.